PENGARUH KECEMASAN MATEMATIKA TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA DI SMAN 5 TAKALAR DITINJAU DARI GENDER - Yuliany, Nur; Rudianto, Rudianto; Mardhiah, Mardhiah; Majid, Ahmad Farham; Munirah, Munirah (Al Asma: Journal of Islamic Education, 2025)
This study aims to determine the description of students' mathematical anxiety and problem-solving abilities at SMAN 5 Takalar and the effect of mathematical anxiety on students' problem-solving abilities at SMAN 5 Takalar in terms of gender. This study uses an ex post facto research type with a quantitative approach. This study was conducted at SMAN 5 Takalar with a population of 310 class X students, with 9 classes. The sample in this study was class X3, with 34 students selected using a simple random sampling technique. The instruments used in this study were a mathematical anxiety questionnaire to determine students' mathematical anxiety and a test to determine students' problem-solving abilities. The data analysis techniques used were descriptive statistical analysis and inferential statistical analysis in the form of a simple linear regression test. The results of this study indicate: (1) Female students' mathematical anxiety is higher than male students and female students' problem-solving abilities are better than male students, (2) Mathematical anxiety has a significant effect on students' overall problem-solving abilities, both male and female. Therefore, we must pay more attention to the psychology of students, one of which is students' mathematics anxiety as a factor that influences their mathematics learning outcomes.